2020
DOI: 10.1038/s41598-020-65676-9
|View full text |Cite|
|
Sign up to set email alerts
|

Establishing magneto-structural relationships in the solid solutions of the skyrmion hosting family of materials: GaV4S8−ySey

Abstract: The GaV4S8−ySey (y = 0 to 8) family of materials have been synthesized in both polycrystalline and single crystal form, and their structural and magnetic properties thoroughly investigated. Each of these materials crystallizes in the F$$\bar{4}$$ 4 ˉ 3m space group at ambient temperature. However, in contrast to the end members GaV4S8 and GaV4Se8, that undergo a structural transition to the R3m space group at 42 and 41 K respectively, the solid solutions (y = 1 to 7) retain cubic symmetry down to 1.5 K. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(55 citation statements)
references
References 63 publications
19
36
0
Order By: Relevance
“…In conclusion, our results show that magnetic order is preserved for low levels of substitution in GaV 4 S 8−y Se y at both ends of the series in contrast to higher levels where spin glasslike behavior is observed [21,22]. On the Se-rich end of the series, the presence of S simply leads to an increase in the width of the local magnetic-field distribution, which is enough to prevent observation of the effect of the SkL in our TF measurements.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…In conclusion, our results show that magnetic order is preserved for low levels of substitution in GaV 4 S 8−y Se y at both ends of the series in contrast to higher levels where spin glasslike behavior is observed [21,22]. On the Se-rich end of the series, the presence of S simply leads to an increase in the width of the local magnetic-field distribution, which is enough to prevent observation of the effect of the SkL in our TF measurements.…”
mentioning
confidence: 51%
“…Polycrystalline samples of GaV 4 S 8−y Se y were synthesized and characterized as described in Refs. [21,22]. Whereas polycrystalline samples are likely to exhibit a different magnetic phase diagram to those of single crystals (whose behavior varies depending on the alignment between applied field and crystallographic axes), we have previously shown that the SkL can be identified unambiguously [21].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…‡ G.Balakrishnan@warwick.ac.uk have been extensively studied as skyrmion hosts [2,3,6,24]. Both GaV 4 S 8 and GaV 4 Se 8 are isostructural with a structural phase transition from a high-temperature cubic F43m phase to a low-temperature rhombohedral R3m structure at 42 and 43 K, respectively, with a further magnetic transition at 13 and 18 K, respectively [17,23].…”
Section: Introductionmentioning
confidence: 99%
“…In this structure, there are two distinct sites on which the chalcogenides can sit: either the S1/Se1 site within the V 4 X 4 cluster or the S2/Se2 site within the GaX 4 tetrahedra. It has been suggested that the cubic-to-rhombohedral phase transition is driven by such mechanisms as a cooperative Jahn-Teller distortion [25] and charge order of the V 4 cluster formed of three V 3+ and one V 4+ ion [24]. In the low-temperature rhombohedral phase a single V ion distorts along the one of the four possible cubic 111 directions in the V 4 X 4 cluster.…”
Section: Introductionmentioning
confidence: 99%